PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3) DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA PERAWAT DI RUMAH SAKIT SANSANI PEKANBARU - Rahmah, Yulia; Andini, Frini Karina (Komunitas Manajemen Kompetitif, 2025)
The purpose of this study is to find out more about the work productivity of nurses at Sansani Hospital, Pekanbaru, in relation to occupational safety and health (K3) and work discipline. Occupational safety and health (K3) and work discipline are independent variables while nurse work productivity is the dependent variable. The sample in this study was determined to be 81 respondents from 102 populations measured using the Slovin formula. This type of research is quantitative research using questionnaire data collection techniques. The data obtained from the results of the questionnaires distributed used incidental sampling techniques which were then processed for further study using the SPSS 25 program. The results of the tests carried out showed that occupational safety and health (K3) had an influence on nurse productivity, where tcount 3,470 > ttable 1,990 and sig 0,000 < 0.05, then work discipline had an influence on nurse work productivity, where tcount 9,123 > ttable 1,990 and sig 0,000 < 0.05, and occupational safety and health (K3) and work discipline on nurse work productivity, with fcount 61 558 > ftable 3 114, and sig 0.000 < 0.05.